Perosomus Elumbis Monster- A Case Report - Baddi, S Y; Gowda, K Hemanna; Mahendra, A M; Ramkrishna, V (Indian Journal of Veterinary Anatomy, 2012)
In the present case, the birth of a perosomus elumbis in HF cow was a unique occurrence which was characterized by lack of vertebrae and spinal cord caudal to the thoracic region along with deformed pelvis and hind limbs.